2020
DOI: 10.4102/sajid.v35i1.196
|View full text |Cite
|
Sign up to set email alerts
|

Description of non-polio enteroviruses identified in two national surveillance programmes in South Africa

Abstract: Background: Human enteroviruses (EV) consist of 106 serotypes and four species: EV-A, EV-B, EV-C and EV-D. Enteroviruses cause clinical symptoms varying from severe to mild. Knowledge of EV burden in South Africa is limited, and as non-polio EV are important causes of acute flaccid paralysis (AFP) and meningitis, information on the circulating serotypes is vital.Methods: Between 2010 and 2012, a total of 832 stool and viral isolate specimens were obtained from two national surveillance programmes at the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The distribution of EV species in our study ( Figure 4 ) was similar to that observed in many countries of the world in different climatic zones according to the results of AFP surveillance [ 31 , 32 , 34 , 36 , 37 , 38 ], investigation of healthy children [ 38 , 39 , 40 ], surveillance of EVs [ 41 ], and rotavirus surveillance [ 32 ]. After 2010, the proportion of EV-A steadily began to increase among both AFP and EVI isolates ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The distribution of EV species in our study ( Figure 4 ) was similar to that observed in many countries of the world in different climatic zones according to the results of AFP surveillance [ 31 , 32 , 34 , 36 , 37 , 38 ], investigation of healthy children [ 38 , 39 , 40 ], surveillance of EVs [ 41 ], and rotavirus surveillance [ 32 ]. After 2010, the proportion of EV-A steadily began to increase among both AFP and EVI isolates ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 85%
“…During the 24 years of this study, the incidence of NPV isolation ranged from 0.3 to 7.7%, on average 3.6% for any virus and 2.5% for NPEVs. This is significantly lower than the frequency of virus isolation from AFP patients in some countries of Asia and Africa, which could be above 60% [31][32][33], and is comparable or somewhat lower than the frequency determined in some countries of the European Region [34,35]. It is noteworthy that NPEV isolation rates can be used to evaluate the efficiency of surveillance, but the reference regions should be matched in terms of socio-economic and environmental conditions.…”
Section: Discussionmentioning
confidence: 73%
“…This century has so far seen around 30 per cent in addition to EV genus. Other than Bangladesh and India, EV-B88 detection has also been reported from Ghana in association with enteric disease in children 18 , Western Cape province of South Africa in a rotavirus surveillance programme 19 and Thailand (acute gastroenteritis in children) along with some other gastroenteritis virus with a prevalence of 1.5 per cent in the group affected 20 . Not much has been reported on EV-B88, except detections in association with AFP and gastroenteritis.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, Enterovirus B species is the largest and most prevalent species of the enteroviruses, so the chances of being detected might be higher than with the other Enterovirus species. 18,33,35 Last, detection and typing methods could be biased towards Enterovirus B species. To eliminate Enterovirus B species bias, a cell culture independent detection and typing method was suggested by Nix et al 20 In the past Enterovirus B species bias was noted because viruses from clinical specimens were cell cultured in a Rhabdomyosarcoma cell line, which showed a greater susceptibility to Enterovirus B species in comparison to other Enterovirus species.…”
Section: Discussionmentioning
confidence: 99%
“…Since Enterovirus B species is the major cause of encephalitis and meningitis cases, it is probably more likely to be detected in cerebrospinal fluid. In addition, Enterovirus B species is the largest and most prevalent species of the enteroviruses, so the chances of being detected might be higher than with the other Enterovirus species 18,33,35 . Last, detection and typing methods could be biased towards Enterovirus B species.…”
Section: Discussionmentioning
confidence: 99%